2020
DOI: 10.3389/fphar.2020.00528
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Lipid-Lowering Mechanisms and Active Ingredients of Danhe Granule on Hyperlipidemia Based on Systems Pharmacology

Abstract: Objective: Investigate the active ingredients and underlying hypolipidemic mechanisms of Danhe granule (DHG). Methods: The lipid-lowering effect of DHG was evaluated in hyperlipidemic hamsters induced by a high-fat diet. The ingredients absorbed into the blood after oral administration of DHG in hamsters were identified by ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS). A systems pharmacology approach incorporating target prediction and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Traditional Chinese Medicine have been applied for treatment of various diseases including HLP and cardiovascular disease with a history of more than 2000 years. Chen indicated that Danhe Granule, a traditional Chinese medicine formula, exhibited excellent hypolipidemic effects in diet‐induced HLP hamsters [39] . Meanwhile, they isolated and identified six active components including EM in the hamster blood, and found that these active components may modulate some key targets (SREBP‐1, SPEBP‐2, LDLR, and so on) involved in lipid metabolism‐related pathways through systemic pharmacological analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional Chinese Medicine have been applied for treatment of various diseases including HLP and cardiovascular disease with a history of more than 2000 years. Chen indicated that Danhe Granule, a traditional Chinese medicine formula, exhibited excellent hypolipidemic effects in diet‐induced HLP hamsters [39] . Meanwhile, they isolated and identified six active components including EM in the hamster blood, and found that these active components may modulate some key targets (SREBP‐1, SPEBP‐2, LDLR, and so on) involved in lipid metabolism‐related pathways through systemic pharmacological analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also have shown that chenpi can reduce the gain of body weight, organ weight, and accumulation of lipid ( 37 ). Obesity is closely related to hyperlipidemia, and reducing the content of serum triglyceride can effectively alleviate hyperlipidemia ( 38 ). There was no significant change in body weight and liver weight in our study, perhaps because the feeding time was not long enough.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that activation of LXR activity could reduce TC, which is responsible for hyperlipidemia [8,1]. Many LXRβ agonists have already been screened such as T0901317 and LXR623 [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…One of the causes of hyperlipidemia is high level of TC, which is tightly regulated by liver X receptor (LXR) [1,8]. LXR is a nuclear receptor with two isoforms, LXRα and LXRβ.…”
Section: Introductionmentioning
confidence: 99%